Prevalence of knee arthritis and role of synovial fluid aspiration in its improvement among patients with musculoskeletal brucellosis in Erbil - Khalid A.O AL- Dabbagh (University of Mosul, 2010)
The study was conducted to record the prevalence and necessity regarding joint aspiration among patients with brucella knee arthritis and its role in the process of improvement. This study was a prospective analysis of 150 patients with musculoskeletal brucellosis (M-S brucellosis) recorded in the period from May 2005-July 2008 (39 months) in Erbil governorate, which cavers population of more than one million. Out of 150 cases; 30 patients who developed knee arthritis (20%) subjected to a comparative study and analysis to determine its prevalence and characters and the role of synovial fluid aspiration in the improvement. Out of the thirty; 18 patients (60 %) were females and 12 patients (40 %) males, the age group between 20-40 years. All patients met the criteria of the diagnosis and all patients were received anti -brucella antibiotic, 15 patients subjected to aspiration of the fluid and they were compared with reminders who were not subjected to fluid aspiration. P value was not significant in both aspirated & non aspirated group after 6th, 8th, 10th and the end of the twelve weeks. In conclusion, M-S brucellosis is common in Erbil. Brucella knee arthritis represents about 20% of musculoskeletal manifestation of Brucellosis. Serial joint aspirations of synovial fluid did not play any role in the improvement of patients. Aspiration of synovial fluid may help in the diagnosis rather than a step for treatment.